Apologia pro Vitis Veteriorum Hominum - Hilton, Boyd (The journal of ecclesiastical history, 1999)
The Oxford Movement in context. Anglican High Churchmanship, 1700–1857. By Peter Benedict Nockles. Pp. xvii+342. Cambridge: Cambridge University Press, 1994. £40 (cloth), £15.95 (paper). 0 521 38162 2; 0 521 58719 0This book, together with subsequent articles on Scotland and Ireland, contains the fruits of researches which first became available in Dr Nockles's Oxford DPhil. of 1982, probably the most widely consulted dissertation on religious developments in eighteenth- and nineteenth-century Britain since John Walsh's Cambridge PhD of 1956. The outlines of the argument have been adumbrated elsewhere, but God (in Nockles's case) resides also in the details, and historians will turn to this book for its rich scholarship and its staggering mastery of published and unpublished sources. Indeed the appearance of this definitive study is doubly welcome because, so long as it was known to be in the offing, there was a danger that other historians would be deterred from starting research on the subject of Anglican High Churchmanship, but now that it is out it will inevitably act as a guide and stimulus to further inquiry. Already scholars such as Stewart Brown, Arthur Burns, Frances Knight, Simon Skinner and Brian Young are beginning to till the ground. A field which had once seemed high and dry has been refreshed and made fertile.